IMPROVING VOCABUALARY ACHIEVEMENT THROUGH TOTAL PHYSICAL RESPONSE AMONG GRADE FOUR ELEMENTARY SCHOOL PUPILS - Katemba, Caroline V.; Tampubolon, Kisan (Journal of Language Pedagogy, 2011)
This research is on Improving Vocabulary Achievement Through Total Physical Response (TPR) among Grade Four Karyawangi Elementary School Pupils. It is administered to answer questionâIs TPRÂ  method effective in improving the vocabulary achievement of the pupils?â The data were collected through pre test and post test, administered to 31 students and was analyzed by using t-test.Â  The achievements showed that the mean of the pre-test was 23.06 and the mean of the post-test was 64.11, while the significant = 0.003 < Î± = 0.05, thus the conclusion that there is a significant difference in pupilsâ vocabulary achievement through Total Physical Response (TPR).